An early assessment of the efficacy of medicines in the treatment of patients with COVID-19 - A. S. Kolbin (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Coronavirus infection 2019 is considered a modern challenge to the world community. In the absence of vaccines and antivirals, effective and safe medicines are an urgent request from the healthcare system. We have evaluated the medical technologies for COVID-19 which are being examined. The search was conducted on the СlinicalTrials.gov at the beginning of April 2020. As a result it was shown that the growth of new clinical trials in the world devoted to COVID-19 is growing by 65% per week. More often, interventional clinical trials of the II and III phases are carried out. Most studies are planned or conducted in Western Europe (n = 92), China (n = 79), and the United States (n = 51). Surrogate points are usually evaluated, such as: clinical recovery, symptom-based disease relief (fever, cough, diarrhea, myalgia, shortness of breath), lack of progression of shortness of breath, rate of artificial ventilation, rate of admission to the intensive care unit, etc. It is antimalarial drugs that are mainly studied. Currently, it is not possible to discuss the efficacy and safety of a drug in the treatment of COVID-19, as most studies have just begun. The therapeutic regimens proposed now in clinical recommendations have no evidence base, and the studies indicated in them are at best considered hypothesizing.